Incidence and management of hypotension in spinal anaesthesia in urological pelvic surgery - Ibraheem, Adil; Alzubaidi, Mazin Abdullateef; Muhsen, Muhammed Ibrahim; Almusawi, Ali Abbas Hashim; Makki Al-Hindy, Hayder Abdul-Amir (Pharmakeftiki, 2025)
The management of hypotension in specific clinical contexts frequently involves the administration of ephedrine; a vasopressor with demonstrated efficacy across multiple scenarios: spinal anaesthesia for uro-pelvic surgery, caesarean section, renal transplantation, and select cases of autonomic dysfunction. Recent evidence suggests that ephedrine use may delay the onset of hypotension. This prospective study has evaluated the incidence and management of hypotension in 80 adult patients (aged 17–45 years) undergoing urological pelvic surgery under spinal anaesthesia. Participants were recruited from the Hilla Teaching Hospital and the Al-Imam Al-Sadeq Teaching Hospital (Iraq) between June 2023 and December 2024, and were randomly assigned to receive either intravenous fluids alone or in combination with ephedrine. Systemic blood pressure was monitored at four time points: preoperatively, following intervention, after anaesthesia induction, and postoperatively. Compared to fluid administration alone, the ephedrine-treated group exhibited significant changes in both systolic and diastolic blood pressure values (p<0.05). These findings suggest that ephedrine enhances haemodynamic stability during spinal anaesthesia and may play a clinically significant role in the intraoperative management of hypotension.